The value of caregiver inclusive practices in geriatric transitions of care: A systematic review. Issue 7 (July 2021) - Meulenbroeks, Isabelle; Epp, Joanne; Schroeder, Liz
Abstract: Globally, hospital length of stay is decreasing, yet the number of aged patients requiring complex care is increasing. This causes more patients, and their informal caregivers, to self-manage in the community following acute care discharge. This study aims to assess whether transitional care programs that integrate caregivers provide better value care than routine care. In this systematic review, Medline Ovid, EMBASE Ovid, CINAHL EbscoHOST, Scopus, and Proquest were searched for any study design that investigated a caregiver inclusive transitional care intervention in a population of people with geriatric syndrome, enroled a comparator group, and assessed population health, experience, and/or cost related outcomes. Risk of bias was assessed by two reviewers using ROBINS I and RoB 2. The review included 23 studies and results were mixed. Consistently positive results occurred for patient and caregiver satisfaction. Cost tended to increase with caregiver inclusive practices. Most studies found no difference in population health outcomes. There was insufficient evidence on healthcare professional experience. Currently, there is insufficient evidence to determine whether caregiver inclusive transitions of care provide better value care than routine care. Studies that rigorously implement and evaluate caregiver inclusive care models are urgently required to inform future policy.